The Effect of Post-Traumatic Training on Community Resilience in the Covid-19 Pandemic in Tabanan Tourism Village - Suindrayasa, I Made; Manangkot, Meril Valentine (Journal of A Sustainable Global South, 2023)
The Covid-19 pandemic has had a stressful and traumatic impact on tourism practitioners in Bali. A pandemic requires people to adapt and have strong resilience to pandemic conditions. In order to increase the capacity of community resilience, actions and methods are needed to be given to the community. Post-Traumatic Training is an effort to improve community resilience. Tabanan tourist village is one of the community-based tours in Bali. The formulation of the research problem is whether there was an effect of Post-Traumatic Training on community resilience during the Covid-19 Pandemic in the Tabanan Tourism Village. The purpose of this study was to determine the effect of Post-Traumatic Training on community resilience during the Covid-19 Pandemic in the Tabanan Tourism Village. The method in this study is analytic descriptive method with a quasi-experimental method with a pre-post test with a control group. The sample of this research is the respondent who resides/lives in the Tourism Village area of ??Tabanan Regency. The sample was divided into 30 experimental groups and 30 control groups. The experimental group was given Post-Traumatic Training, while the control group did not receive Post-Traumatic Training. Collecting data using a resilience questionnaire. Data were analyzed using the Wilcoxon test. The results of the study obtained a p-value <0.05 which means that there was an effect of post-traumatic training on community resilience during the Covid-19 pandemic in the Tabanan Tourism Village. The suggestion from this research is that it is hoped that this post-traumatic training program can be continued on an ongoing basis and can be disseminated to tourist villages in other regions.